Eine trilinguale ʿEzana-Inschrift - Uhlig, Siegbert (Aethiopica, 2001)
Ever since the ʿEzana inscriptions were published by the Deutsche Aksum Expedition in the beginning of the 20th century they have been looked upon as the most important document from Ethiopia of the 4th century A.D. Today, however, another stele has been discovered, which, having similar content — repeated in three languages: Pseudosabaic, Greek and Gǝʿǝz — is in a much better state. The text in its turn, though in many aspects identical, shows a row of distinct deviations from the DAE stele, which makes it necessary to critically compare the two texts. The fact, that the stone was originally placed in the middle of a grave site, as well as the palm frond and the monotheistic phrase “Lord of the Heaven” used in the text indicate that by that time the Aksumite court had been converted to Christianity.